2021
DOI: 10.1101/2021.07.26.453861
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Alzheimer’s gene SORL1 is a regulator of endosomal traffic and recycling in human neurons

Abstract: Background: Loss of the Sortilin-related receptor 1 (SORL1) gene seems to act as a causal event for Alzheimer's disease (AD). Recent studies have established that loss of SORL1, as well as mutations in autosomal dominant AD genes APP and PSEN1/2, pathogenically converge by swelling early endosomes, AD's cytopathological hallmark. Acting together with the retromer trafficking complex, SORL1 has been shown to regulate the recycling of the amyloid precursor protein (APP) out of the endosome, contributing to endos… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 94 publications
(161 reference statements)
0
2
0
Order By: Relevance
“…Retromer is considered a “master conductor” of endosomal trafficking ( Burd and Cullen, 2014 ) because it regulates the two pathways whereby cargo is recycling out of endosomes: from the endosome back to the cell surface, and from the endosome back to the TGN ( trans -Golgi network). APP and GluA1 are neuronal endosomal cargo that typify the first pathway, and based on older ( Small and Petsko, 2015 ) and newer studies ( Mishra et al, 2021 ), SORL1 (sortilin-related receptor1) can act a retromer-receptor that allows the retromer coat to interact with this cargo. We, therefore, took advantage of our depletion-repletion paradigm to investigate SORL1.…”
Section: Resultsmentioning
confidence: 99%
“…Retromer is considered a “master conductor” of endosomal trafficking ( Burd and Cullen, 2014 ) because it regulates the two pathways whereby cargo is recycling out of endosomes: from the endosome back to the cell surface, and from the endosome back to the TGN ( trans -Golgi network). APP and GluA1 are neuronal endosomal cargo that typify the first pathway, and based on older ( Small and Petsko, 2015 ) and newer studies ( Mishra et al, 2021 ), SORL1 (sortilin-related receptor1) can act a retromer-receptor that allows the retromer coat to interact with this cargo. We, therefore, took advantage of our depletion-repletion paradigm to investigate SORL1.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, late-onset risk genes such as BIN1 , PICALM , CD2AP and SORL1 play various functions in endosomal trafficking [ 25 , 32 35 ]. Cell biology studies from our group and others demonstrated that proteins such as Retromer [ 36 ] and its associated receptor, SORL1, play a key role in the trafficking of cargo out of the endosome towards the plasma membrane [ 37 39 ], a process impaired in AD and critical for neuronal function. These discoveries reveal a promising avenue for biomarker development focused on endosomal trafficking, which we are currently investigating [ 40 ].…”
Section: Disruption Of the Endo-lysosomal System In Neurodegenerative...mentioning
confidence: 99%